Depredation capacity of Chrysoperla carnea on Nysius sp. pest of Chenopodium quinoa, laboratory level in the irrigation Majes - Arequipa 2017 - Dina Beatriz Mamani Gutierrez (2019)
The present research work was developed in the AUTODEMA laboratory in Majes Irrigation in 2017, in order to evaluate the predation capacity of Chrysoperla carnea (Larva III) as biological controller of Nysuis sp. in its nymphal and adult stages; in the cultivation of quinoa in Majes Irrigation, being the main objective of the investigation. In order to carry out this experimentation, they obtained Chrysoperla carnea species from the Biological Control Laboratory of the National Agrarian Health Service SENASA - Lima, carrying out a mass breeding in their different stages and obtaining individuals from Nysius sp., collecting insects of the quinoa areas of the Majes Irrigation; which were reared in laboratory conditions. To evaluate the predation capacity of the species mentioned above, a study was carried out where two T1 treatments (Nysius sp. Nymphs) and T2 (Nysius sp. Adults) were taken. Both treatments had 5 repetitions and the evaluation was carried out for 5 days. consecutive until the total lacewings larvae went to pupal status, which concluded the evaluations. The obtained results indicate that Chrysoperla carnea in its larval stage III is the most voracious on nymphs that adutos of Nysius sp .; where a larva throughout its larval stage III depredates on average 25 nymphs and 9 adults.